Extremely conductive RuO2-coated LiNi0.5Mn1.5O4 for lithium-ion batteries. (1st April 2017) - Jung, Sung Hoo; Kim, Dong Hyeon; Brüner, Philipp; Lee, Hyeyoun; Hah, Hoe Jin; Kim, Seok Koo; Jung, Yoon Seok
Graphical abstract: Extremely conductive RuO2 -coated LiNi0.5 Mn1.5 O4 (0.27 S/cm, 0.57 wt%) enables high rate capability for thicker electrode with less amount of carbon with improved durability. Highlights: RuO2 is coated on LiNi0.5 Mn1.5 O4 (LNMO) particles via a wet chemical route. Extremely high conductivity of 0.27 S/cm is achieved by coating 0.56 wt% RuO2 . It is evidenced that high conductivity of RuO2 leads to enhanced rate performance. The improvements are dramatic for a thicker electrode with low carbon content. Excellent stability of RuO2 that enables improved durability is confirmed. Abstract: An unprecedentedly high electronic conductivity of 0.27 S cm −1 is achieved by depositing 0.56 wt% crystalline RuO2 on LNMO via a wet-chemical route. Systematic assessment of the electrochemical performance of bare and RuO2 -coated LNMO electrodes unambiguously demonstrates that the high electronic conductivity of RuO2 enables significant enhancement in rate capability. These improvements are dramatic for the electrodes in which extremely low amounts of carbon additives are included and/or the loading amount is high. This finding highlights the importance of electronic conduction in composite electrodes, not only for high power but also for high energy density. The RuO2 -coated LNMO electrode with 1 wt% carbon additives exhibits a high capacity of 100 mA h g −1 at 1C in the range 3.0–5.0 V (vs. Li/Li + ). This result is in sharp contrast to the negligible capacity exhibited by the bare LNMO electrode. In addition, the chemical/electrochemical stability of the RuO2 coating under repeated cycling is confirmed, explaining the observed improvement in durability of the RuO2 -coated LNMO over the bare LNMO.